Pembrolizumab-Mediated Complete Remission of a PLA2R-Positive Paraneoplastic Membranous Nephropathy: A Case Report - Rayane Benyahia; Magali Colombat; Serigne Gueye; Julien Mazières; Julie Belliere (Kidney Medicine)
Management of paraneoplastic membranous nephropathy (MN) is directed toward the underlying malignancy, and prescriptions of immune checkpoint inhibitors (ICIs) are skyrocketing in the field of oncology. However, this drug category is usually discouraged for patients with autoimmune disorders (AIDs) because it might trigger immune-related adverse events (irAEs) in the form of flare-ups or even genesis of AID. Yet, nothing is known about the efficacy and safety of ICIs for cancers associated with paraneoplastic MN. Here, we report a rare case of PLA2R-positive MN related to a PDL1-positive locally advanced lung adenocarcinoma. Antineoplastic treatment with the anti-PD1 pembrolizumab as a first-line, single-drug therapy allowed for both cancer and nephropathy remissions. To date, to our knowledge, this is the first description of a (PLA2R-positive) paraneoplastic MN that was put into remission via an ICI monotherapy successfully targeting the associated neoplasia only, without additional immunosuppressive agents.